Effects of isolated or enriched housing at adolescence upon ethanol intake and anxiety responses, in rats exposed to prenatal ethanol - Di Doi, Paula Luciana (2019)
Prenatal alcohol exposure (PAE) is highly prevalent worldwide, and can affect alcohol intake and anxiety responses in the offspring. It is still relatively unknown how PAE interacts with stress exposure at adolescence, and there is a scarcity of treatments to reduce the impact of PAE. The present study assessed alcohol (ethanol) intake and anxiety responses after PAE and tested the modulation of these responses by different housing conditions during early adolescence. Pregnant dams were exposed for 22 hours/day, from gestational day 0, throughout pregnancy, and until postnatal day 7 (PD 7), to a single bottle of 10% ethanol that was mixed in tap water and sucralose (EtOH Group), or to a single bottle of tap water and sucralose (CTRL Group). During PDs 21-42 the offspring was exposed to standard pair housing, isolated housing or enriched housing. Immediately after, they were pair-housed and tested for ethanol intake in 24-hour access, intermittent 2-bottle choice sessions conducted over 4 weeks, and for anxiety responses in the light-dark box test. The EtOH offspring exhibited heightened anxiety (i.e., greater avoidance of the white area of the light-dark box) at PD21, when compared to control (CTRL) rats. Isolated housing induced greater avoidance of the white area, when compared to standard or enriched housing, on PDs 42 and 70. There were no significant EtOH versus CTRL differences in relative (i.e., percent preference vs. water) ethanol intake, yet overall fluid intake and absolute (g/kg) ethanol intake were significantly lower in EtOH versus CTRL rats. Enriched housing during adolescence had a suppressing effect upon absolute ethanol intake during the first week of testing, an effect more noticeable in CTRL than in PAE rats. The present study indicates that PAE or isolated housing is associated with an anxiety-like phenotype. The protracted PAE protocol here employed caused a generalized reduction of intake behaviours. Environmental enrichment was associated with a subtle, yet significant, reduction in absolute ethanol intake.